Induction and nosocomial dissemination of carbapenem and polymyxin-resistant Klebsiella pneumoniae - Gilberto Gambero Gaspar; Fernando Bellissimo-Rodrigues; Leonardo Neves de Andrade; Ana Lúcia Darini; Roberto Martinez (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
INTRODUCTION: Polymyxins are antimicrobial agents capable of controlling carbapenemase-producing Klebsiella pneumoniae infection. METHODS: We report a cluster of four patients colonized or infected by polymyxin-resistant and Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae. RESULTS: Three patients were hospitalized in adjacent wards, and two were admitted to the intensive care unit. The index case maintained prolonged intestinal colonization by KPC-producing K. pneumoniae. Three patients received polymyxin B before the isolation of polymyxin-resistant K. pneumoniae. CONCLUSIONS: Colonization by KPC-producing K. pneumoniae and previous use of polymyxin B may be causally related to the development of polymyxin-resistant microorganisms.